# Expansion of cos (A + B + C)

We will learn how to find the expansion of cos (A + B + C). By using the formula of cos (α + β) and sin (α + β) we can easily expand cos (A + B + C).

Let us recall the formula of cos (α + β) = cos α cos β - sin α sin β and sin (α + β) = sin α cos β + cos α sin β.

cos (A + B + C) = cos [(A + B) + C]

= cos (A + B) cos C - sin (A + B) sin C, [applying the formula of cos (α + β)]

= (cos A cos B - sin A sin B) cos C - (sin A cos B + cos A sin B) sin C, [applying the formula of cos (α + β) and sin (α + β)]

= cos A cos B cos C - sin A sin B sin C - sin C sin A cos B - sin B sin C cos A, [applying distributive property]

= cos A cos B cos C (1 - tan A tan B - tan C tan A - tan B tan C)

Therefore, the expansion of cos (A + B + C) = cos A cos B cos C (1 - tan A tan B - tan C tan A - tan B tan C)

### New! Comments

Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.

Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.